Implementasi Model Blended Learning pada Mata Pelajaran Matematika dengan Media Whatsapp Peserta Didik di Sekolah Dasar - Septiani, Sela; Prastowo, Andi (AR-RIAYAH: Jurnal Pendidikan Dasar, 2024)
Blended learning is a learning model that combines face-to-face learning with online learning. After the end of Covid-19, teachers continued to implement technology-based learning using WhatsApp media to introduce technology without abandoning face-to-face learning. This research aims to describe the implementation of blended learning models in mathematics subjects using WhatsApp media for students in elementary schools. This research uses a qualitative approach. Research conducted by researchers at Depok 1 State Elementary School on class IV students totaling 27 students. Data collection was obtained through interviews and observations. The research results showed that interactions that occurred via WhatsApp media facilitated discussions between teachers and students outside of face-to-face learning time. Planning is done by selecting materials, implementation is done by sending materials via WhatsApp, and evaluation is done by giving tests. Apart from that, WhatsApp also has obstacles, namely network constraints, support factors and parental control while in the home environment. The implications of the blended learning model using WhatsApp media are appropriate to apply, because WhatsApp is a familiar media and is one of the media that is easy to use. Technological developments are increasingly rapid, so teachers can introduce technology for education to students.